2016
DOI: 10.1103/physrevd.94.034501
|View full text |Cite
|
Sign up to set email alerts
|

Rho resonance parameters from lattice QCD

Abstract: We perform a high-precision calculation of the phase shifts for π-π scattering in the I = 1, J = 1 channel in the elastic region using elongated lattices with two mass-degenerate quark flavors (N f = 2). We extract the ρ resonance parameters using a Breit-Wigner fit at two different quark masses, corresponding to mπ = 226 MeV and mπ = 315 MeV, and perform an extrapolation to the physical point. The extrapolation is based on a unitarized chiral perturbation theory model that describes well the phase-shifts arou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
182
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(210 citation statements)
references
References 71 publications
(144 reference statements)
25
182
3
Order By: Relevance
“…In particular, the Lüscher method and its extensions for relating finite-volume spectra to scattering amplitudes are now well established for elastic [5][6][7][8][9][10][11][12][13][14] and coupled-channel [15][16][17][18][19] hadron-hadron scattering. These methods have been demonstrated in a number of applications, notably for the ρ-resonance seen in P -wave ππ scattering [20][21][22][23][24][25][26][27][28][29], and for the σ resonance seen in S-wave ππ scattering [30]. It has also recently been shown that, with sufficiently extensive and precise spectra, information on coupled-channel hadron-hadron scattering amplitudes can be obtained [26,[31][32][33] -this is crucial for understanding highly excited states that are typically kinematically permitted to decay into several channels.…”
Section: Jhep10(2016)011mentioning
confidence: 99%
“…In particular, the Lüscher method and its extensions for relating finite-volume spectra to scattering amplitudes are now well established for elastic [5][6][7][8][9][10][11][12][13][14] and coupled-channel [15][16][17][18][19] hadron-hadron scattering. These methods have been demonstrated in a number of applications, notably for the ρ-resonance seen in P -wave ππ scattering [20][21][22][23][24][25][26][27][28][29], and for the σ resonance seen in S-wave ππ scattering [30]. It has also recently been shown that, with sufficiently extensive and precise spectra, information on coupled-channel hadron-hadron scattering amplitudes can be obtained [26,[31][32][33] -this is crucial for understanding highly excited states that are typically kinematically permitted to decay into several channels.…”
Section: Jhep10(2016)011mentioning
confidence: 99%
“…A simulation close to the physical point was carried out by the RQCD Collaboration [18]. The GWU group extracted very precise phase shifts for two different pion masses (M π ≈ 226 MeV and ≈ 315 MeV) [19,20]. See also Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In Refs. [20,24], the available N f = 2 lattice data were extrapolated to the physical point using unitarized Chiral Perturbation Theory based on the formulation of Ref. [25] with some modifications.…”
Section: Introductionmentioning
confidence: 99%
“…The large number of lattice data points results from using all lattice irreps for multiple center-of-mass momenta, and multiple lattice volumes. Figure 5 shows the current world data for g ρππ from the lattice determinations [10][11][12][13][14][15][16][17][18]. While there is in general a good agreement among the lattice data, the uncertainties in the plot are (in most cases) statistical only and there is no calculation demonstrating a full control of systematic uncertainties.…”
Section: The ρ Mesonmentioning
confidence: 99%
“…After a pioneering study by the CP-PACS collaboration [9], multiple groups provided proof of principle calculations demonstrating the feasibility of lattice resonance studies [10][11][12]. In the meantime a number of further studies exist [13][14][15][16][17][18]. Figure 4 shows an example of a state-of-the-art calculation by the Hadron Spectrum Collaboration [15].…”
Section: The ρ Mesonmentioning
confidence: 99%